MINA53 deficiency leads to glioblastoma cell apoptosis via inducing DNA replication stress and diminishing DNA damage response. Issue 11 (November 2018) - Xuan, Fan; Huang, Mengying; Zhao, Erhu; Cui, Hongjuan
Abstract MYC-induced nuclear antigen (MINA53) is a JmjC (jumonji C domain)-containing protein, which is highly expressed in many cancers including glioblastoma. We have revealed in our previous report that MINA53 is a poor prognostic indicator for glioblastoma patients, and knockdown of MINA53 could reduce glioblastoma malignancy. In this study, we found that MINA53 knockdown could decrease the DNA replication initiation in glioblastoma cells. Through further investigations, we revealed that MINA53 could regulate the expression of the CDC45-MCM-GINS (CMG) complex genes, which are vital for DNA replication initiation. Knockdown of MINA53 reduced the CMG genes expression and thus induced DNA replication stress and DNA damage. Furthermore, MINA53 knockdown diminished DNA damage response (DDR) by reducing the ATM/ATR-H2AX pathway activity and finally led glioblastoma cells to apoptosis and death. We further applied a genotoxic drug Doxorubicin and found that MINA53 deficiency sensitized glioblastoma cells to Doxorubicin. Our study reveals that MINA53 is involved in DNA replication initiation and DNA damage response, and provides support for MINA53 as a novel and potential therapeutic target for glioblastoma treatment.